IMPLEMENTASI PENILAIAN OTENTIK DALAM MATA PEMBELAJARAN BAHASA INDONESIA DI SMP NEGERI KOTA PAYAKUMBUH - Khairani, Risma; Atmazaki, Atmazaki,; Abdurahman, Abdurahman (Universitas Negeri Padang, 2018)
Â ABSTRACTÂ The purpose of this research are three (1) types of authentic assessment used by teachers in Indonesian language subjects in SMP Negeri Payakumbuh, (2) the compatibility between authentic assessment conducted by teachers of Indonesian subjects in SMP Negeri Payakumbuh and theories that exist in Curriculum 2013, (3) the obstacles faced by Indonesian language teachers in SMP Negeri Payakumbuh. This research type is qualitative research using descriptive method. Data collection techniques were conducted by observation, interview, and documentation study. Based on research findings and research results can be concluded the following three things. (1) Overall type of authentic assessment has been used by Indonesian teachers in SMP Negeri Payakumbuh. (2) Overall the appropriateness between authentic assessment of Indonesian language teachers in SMP Negeri Payakumbuh and the theory that existed in the Curriculum 2013 is good. Pthere is a component of the understanding of the process and the assessment of learning based on data obtained in the study is categorized well. Indonesian teachers SMPN 3 Payakumbuh already understand the process and assessment of learning well. Indonesian language teacher SMPN 5 Payakumbuh already understand the process and assessment of learning well. Indonesian teachers SMPN 8 Payakumbuh already understand the process and assessment of learning well. In the component of the implementation of the assessment of learning based on the data obtained in the study categorized quite well. Indonesian language teacher SMPN 3, 5, and 8 Payakumbuh has conducted a fairly good learning appraisal.Â Kata kunci: Implementasi penilaian otentik, bahasa Indonesia